2010
DOI: 10.1103/physreva.82.042511
|View full text |Cite
|
Sign up to set email alerts
|

Atomic excitations during the nuclearβdecay in light atoms

Abstract: Probabilities of various final states are determined numerically for β − -decaying He, Li, and Be atoms. In our evaluations of the final-state probabilities we have used the highly accurate atomic wave functions constructed for each few-electron atom or ion. We also discuss an experimental possibility to observe negatively charged ions which form during the nuclear β + decays. Corrections on direct interaction between atomic electrons and fast β electrons or positrons are considered. It is shown that for our r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 41 publications
2
35
1
Order By: Relevance
“…In his model, the third (recombination) stage of the three-step scenario is partitioned into two steps: the capture of a laser-accelerated electron into an autoionizing state of the parent ion followed by the radiative relaxation of this state to the ground state with emission of the harmonic photon. Although this four-step model provided reasonable estimates for the ratio of the enhanced harmonic intensity to the averaged intensity of neighboring harmonics comparable with those observed in experiment, authors of [56] point out that the suppression of harmonics preceding the resonant one remains a puzzle for the proposed theoretical model.…”
Section: Principles Of High-order Harmonic Generation Of Laser Radiatsupporting
confidence: 59%
See 3 more Smart Citations
“…In his model, the third (recombination) stage of the three-step scenario is partitioned into two steps: the capture of a laser-accelerated electron into an autoionizing state of the parent ion followed by the radiative relaxation of this state to the ground state with emission of the harmonic photon. Although this four-step model provided reasonable estimates for the ratio of the enhanced harmonic intensity to the averaged intensity of neighboring harmonics comparable with those observed in experiment, authors of [56] point out that the suppression of harmonics preceding the resonant one remains a puzzle for the proposed theoretical model.…”
Section: Principles Of High-order Harmonic Generation Of Laser Radiatsupporting
confidence: 59%
“…As it was mentioned above, some attempts in explanation of experimental observations of resonance-induced enhancement of single harmonic during plasma HHG have been reported in [43,45,49,[51][52][53][54][55][56][57]. In particular in [53], it has been shown that the influence of atomic autoionizing states on the phase matching of HHG may result in efficient selection of the single harmonic in calcium plasma.…”
Section: Principles Of High-order Harmonic Generation Of Laser Radiatmentioning
confidence: 98%
See 2 more Smart Citations
“…In a previous paper [51] we have calculated the transition probabilities of the transitions from the 1 S ground state of He atom to the first ten low-lying 1 S ground and excited states of the Li + ion using the Hy-CI method, and with them the probability of ionization to the Li 2+ ion. The values of these probabilities have been also determined by the CI method using B-splines orbitals by Wauters and Vaeck [52] and by the full relativistic four-component Dirac-Kohn-Sham (DKS) method by Glushkov [43].…”
Section: B Slater Orbitals and Gaussian Orbitalsmentioning
confidence: 99%